EFFICACY OF INTRAGASTIC BALLOONS IN WEIGHT REDUCTION - Durmishi, Ymer; Salihu, Leminot; Bytyqi, Sami (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
The endoscopic application of intragastric balloons (IGB) is a very effective non-surgical technique in the treatment of excess body weight. The aim of this study was to Ð°nalyze the effectiveness of IGB in obesity treatment and tÐ¾ compare the results of using different types of IGB. The study included 80 overweight patients with a BMI between 25 and 40 kg/m 2 , treated with the application of two types of IGB (Spatz and Endd-Ball). Weight control of patients was performed 48 hours, 7 days, 14 days, 30 days, 90 days, and 180 days after the IGB placement, as well as 6 months after the IGB removal. Six months after application, the IGBs were endoscopically removed. The number of kilograms lost, as well as the change in BMI, were analyzed. A comparison between the results obtained with the two different types of IGB (Spatz and Edd-Ball) was made. For statistical processing of the data, a database was created in the statistical program SPSS for Windows, .The average weight loss 6 months after the application of IGB was about 15 kg. Comparing BMI values â€‹â€‹before and 6 months after the intervention showed a statistically significant decrease in BMI after the intervention (p= 0.00) and confirmed the efficacy of IGB. Comparing the lost kilograms in relation to the type of IGB applied did not show statistically significant differences. The application of IGB has shown to be an effective method for weight loss. Keywords: obesity, intragastric balloon, therapy, endoscopy.